The Soft Agar Colony Formation Assay - Borowicz, Stanley; Van Scoyk, Michelle; Avasarala, Sreedevi; Karuppusamy Rathinam, Manoj Kumar; Tauler, Jordi; Bikkavilli, Rama Kamesh; Winn, Robert A. (Journal of visualized experiments, 2014)
Anchorage-independent growth is the ability of transformed cells to grow independently of a solid surface, and is a hallmark of carcinogenesis. The soft agar colony formation assay is a well-established method for characterizing this capability in vitro and is considered to be one of the most stringent tests for malignant transformation in cells. This assay also allows for semi-quantitative evaluation of this capability in response to various treatment conditions. Here, we will demonstrate the soft agar colony formation assay using a murine lung carcinoma cell line, CMT167, to demonstrate the tumor suppressive effects of two members of the Wnt signaling pathway, Wnt7A and Frizzled-9 (Fzd-9). Concurrent overexpression of Wnt7a and Fzd-9 caused an inhibition of colony formation in CMT167 cells. This shows that expression of Wnt7a ligand and its Frizzled-9 receptor is sufficient to suppress tumor growth in a murine lung carcinoma model.